2019
DOI: 10.1038/s41598-019-51663-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biocompatible Nanosilica on Green Stabilization of Subgrade Soil

Abstract: This study reports the synthesis and potential application of biocompatible silica nanoparticles for subgrade soil stabilization. Nanosilica preparation as a major component from wheat husk ash is systematically studied and confirmed by FTIR, ICP, XRD, and TEM analyses. The produced biogenic nanosilica showed an amorphous structure with an average size of 20 nm. Upon loading various green nanosilica contents, our results show an improvement in the key parameters including Atterberg’s limits, maximum dry densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…The different approaches of green synthesis make use of resources such as microbial systems, plant systems, and biological materials. The demand for green synthesis keeps on increasing since the production of nanoparticles is costeffective and eco-friendly [3,4]. The synthesis of metallic nanoparticles by green route is gaining attention due to the growing microbial resistance of disease-causing microorganisms against antibiotics and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The different approaches of green synthesis make use of resources such as microbial systems, plant systems, and biological materials. The demand for green synthesis keeps on increasing since the production of nanoparticles is costeffective and eco-friendly [3,4]. The synthesis of metallic nanoparticles by green route is gaining attention due to the growing microbial resistance of disease-causing microorganisms against antibiotics and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that the addition of nanosilica stabilizer up to 1.5 % provides the highest amount of the dry density, cohesion, friction angle and CBR value for the subgrade soil which is probably due to the appropriate replacement of nanosilica additive with air in soil pores. An increase in the weight of silica nanoparticles over an optimal of 1.5 % leads to a decrease in the soil parameters as a result of the accumulation and agglomeration of silica (Buazar, 2019). It should be noted that using a high content of nanomaterials such as 10 % (by the weight of base soil) must be accompanied by new mixing methods (which may be introduced in future and do not cause agglomeration) or using some dispersing agents (As it is well known, the agglomeration phenomenon happens in mixing nanoparticles with many materials such as soil, concrete and etc.…”
Section: Unconfined Compressive Strengthmentioning
confidence: 99%
“…For the overall result, for the lime, three studies from [7], [9], and [21] shows the plasticity classification for untreated soil change from high plastic to slightly plastic when the lime was added into the soil while for the other result remains unchanged. For result from [13] and [18] change from high plastic to medium plastic, for the result from [22] that change from medium plastic to slightly plastic, for the result from that change from medium plastic to high plastic and for the result from from [29] was changed from slightly plastic to medium plastic. For the medium plastic result, only the result when added the fly ash shows the increase of plastic classification, which is from medium to high plastic.…”
Section: 1 Basic Datamentioning
confidence: 99%